2003
DOI: 10.18388/abp.2003_3632
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of Ubc9 protein in rat tissues.

Abstract: Ubc9 is a homologue of the E2 ubiquitin conjugating enzyme and participates in the covalent linking of SUMO-1 molecule to the target protein. In this report we describe a simple and efficient method for obtaining pure human recombinant Ubc9 protein. The purified Ubc9 retained its native structure and was fully active in an in vitro sumoylation assay with the promyelocytic leukaemia (PML) peptide as a substrate. In order to better understand the physiology of Ubc9 protein we examined its levels in several rat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Since little (or no) analysis of SUMO tissue distribution has been performed, it is unclear whether the distributions noted here are typical of most vertebrate tissues or are restricted to hibernating animals. However, comparison of rat Ubc9 expression levels in various tissues (Golebiowski et al, 2003) showed interesting parallels with SUMO-1 tissue distributions observed in our ground squirrels that is, the highest expression in spleen, relatively high expression in kidney and liver, and low expression in heart and skeletal muscle.…”
Section: Discussionsupporting
confidence: 74%
“…Since little (or no) analysis of SUMO tissue distribution has been performed, it is unclear whether the distributions noted here are typical of most vertebrate tissues or are restricted to hibernating animals. However, comparison of rat Ubc9 expression levels in various tissues (Golebiowski et al, 2003) showed interesting parallels with SUMO-1 tissue distributions observed in our ground squirrels that is, the highest expression in spleen, relatively high expression in kidney and liver, and low expression in heart and skeletal muscle.…”
Section: Discussionsupporting
confidence: 74%
“…As shown in Fig. 1A, UBC9 transcripts were expressed ubiquitously expressed in bovine tissues including fetal and adult ovaries, consistent with the expression pattern observed in mouse (Azuma et al, 2001), rat (Golebiowski et al, 2003) and human (Yasugi and Howley, 1996),…”
Section: Expression Analysis Of Ubc9supporting
confidence: 85%
“…The findings suggest that ERβ blocked ZAK nuclear translocation to prevent ZAK‐induced hypertrophy by modulating the SUMOylation of ZAK. In addition, the fact that the components of the SUMO conjugation pathway are abundant in the heart indicates the possibility that the SUMO pathway may be implicated in cardiovascular development via modifying the transcription factors indispensable for normal cardiovascular function and development . The results show that Dox treatment to overexpress ZAK induced SUMO‐1 protein expression; however, overexpressed ERβ could totally repress the SUMO‐1 protein level induced by ZAK.…”
Section: Discussionmentioning
confidence: 98%